Excitation spectrum in two-dimensional superfluid 4He: Сверхтекучесть в низкоразмерных системах и в условиях ограниченной геометрии - Arrigoni, F.; Vitali, E.; Galli, D.E.; Reatto, L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
In this work we perform an ab-initio study of an ideal two-dimensional sample of 4He atoms, a model for 4He films adsorbed on several kinds of substrates. Starting from a realistic hamiltonian we face the microscopic study of the excitation phonon–roton spectrum of the system at zero temperature. Our approach relies on path integralground state Monte Carlo projection methods, allowing to evaluate exactly the dynamical density correlationfunctions in imaginary time, and this gives access to the dynamical structure factor of the system S(q,w), containinginformation about the excitation spectrum E(q), resulting in sharp peaks in S(q,w). The actual evaluation of S(q,w) requires the inversion of the Laplace transform in ill-posed conditions, which we face via the genetic inversion via falsification of theories technique. We explore the full density range from the region of spinodal decomposition to the freezing density, i.e., 0.0321 Å–2– 0.0658 Å–2. In particular we follow the density dependence of the excitation spectrum, focusing on the low-wave vector behavior of E(q), the roton dispersion, the strength of single quasiparticle peak, Z(q), and the static density response function, c(q). As the density increases, the dispersion E(q) at low-wave vector changes from a superlinear (anomalous dispersion) trend to a sublinear (normaldispersion) one, anticipating the crystallization of the system; at the same time the maxon–roton structure,which is barely visible at low density, becomes well developed at high densities and the roton wave vector has a strong density dependence. Connection is made with recent inelastic neutron scattering results from highly orderedsilica nanopores partially filled with4He.